(untitled) (Journal of Medicine, 2014)
Sarcoidosis is a systemic granulomatous disease of unknown origin. It is manifested pathologically by the presence of noncaseating granulomas containing multinucleated giant cells,although other granulomatous diseases may produce identical findings. The vast majority of patients have thoracic sarcoidosis with bilateral hilar lymphadenopathy and/or bronchonodular pulmonary infiltrates on chest radiographs. About 40% of patients have extrathoracic disease involving the eye, skin, lymph nodes, liver, spleen, heart, and musculoskeletal or nervous system. Here we report a case of sarcoidosis who presented only with generalized lymphadenopathy. DOI: http://dx.doi.org/10.3329/jom.v15i1.19874 J Medicine 2014; 15: 58-60